Two‐year outcomes on bone density and fracture incidence in patients with T2DM randomized to bariatric surgery versus intensive medical therapy - Maghrabi, Adam H.; Wolski, Kathy; Abood, Beth; Licata, Angelo; Pothier, Claire; Bhatt, Deepak L.; Nissen, Steven; Brethauer, Stacy A.; Kirwan, John P.; Schauer, Philip R.; Kashyap, Sangeeta R. (Obesity (Silver Spring, Md.), 2015)
Objective To determine the 2‐year outcomes of Roux‐en‐Y gastric bypass (RYGB) and sleeve gastrectomy (SG) vs. intensive medical therapy (IMT) on lean body mass, total bone mass, and bone mineral density (BMD) measures from the STAMPEDE trial. Methods 54 subjects (BMI: 36 ± 1 kg/m2, age: 48 ± 4 years) with type 2 diabetes (T2DM) (HbA1c: 9.7 ± 2%) were randomized to IMT, RYGB, or SG and underwent DXA at baseline and at 1 and 2 years. Results At 2 years, the reduction in BMI was similar after RYGB and SG and was greater than IMT (P < 0.001). Lean mass was reduced by ∼10%, total bone mineral content reduced by ∼8%, and hip BMD reduced by ∼9% in both surgical groups and was significantly greater than IMT despite increases in vitamin D intake in all groups. The change in hip BMD correlated with weight loss (r = 0.84, P < 0.0001) and changes in lean mass (r = 0.74, P < 0.0001) and leptin (r = 0.53, P < 0.0001). Peripheral fractures were self‐reported in RYGB (4/18 patients), SG (2/19 patients), and IMT (4/16 patients). Conclusions Surgically induced weight loss is associated with modest reductions in lean mass, bone mineral content, and BMD, despite calcium and vitamin D supplementation in patients with T2DM. Awareness for bone loss is indicated for patients undergoing bariatric procedures.